Hesperetin attenuates ischemia/reperfusion-induced acute kidney injury by regulating ferroptosis in mice - Xiaoyu Xie; Chen Guan; Ningxin Zhang; Chenyu Li; Zengying Liu; Chengyu Yang; Liting Wang; Yan Xu (Renal Failure, 2025)
Background Acute kidney injury (AKI) is a complex syndrome often resulting from ischemia/reperfusion (I/R) injury (IRI). Due to the significant role of ferroptosis in AKI pathogenesis, therapeutic strategies targeting ferroptosis could offer potential benefits in managing AKI. Hesperetin, has shown potential in inhibiting ferroptosis-related pathways, while its role in I/R-induced AKI remains unclear. This study aimed to assess the renoprotective effects of hesperetin on IRI mice and further investigate its underlying molecular mechanism related to ferroptosis.Methods The mice were administered with hesperetin intragastrically for seven consecutive days before 24 h post-bilateral IRI. Serum levels of creatinine and blood urea nitrogen were measured to assess renal function. Histopathological analyses were performed to evaluate tubular injury and cell death. Molecular markers of ferroptosis were quantified. Bioinformatics and molecular docking confirmed hesperetin’s binding affinity with Src, and immunohistochemistry showed altered phosphorylated Src expression in kidneys post-intervention.Results Hesperetin effectively improved renal function and alleviated renal injury. Ferroptosis markers showed that hesperetin decreased levels of ACSL4 while increasing GPX4, FTH1, and SLC7A11, suggesting an anti-ferroptotic effect. The bioinformatics analysis showed proto-oncogene tyrosine-protein kinase Src plays a key factor in the regulation of ferroptosis of hesperetin. Molecular docking revealed that hesperetin binds to Src, and immunohistochemistry confirmed that hesperetin downregulates Src phosphorylation in renal tubular epithelial cells.Conclusion Hesperetin exerts renoprotective effects against I/R-induced AKI by improving renal function and inhibiting ferroptosis. Its therapeutic potential may be attributed to modulation of the Src, making it a promising candidate for AKI treatment.